PENERAPAN MODEL PEMBELAJARAN TREFFINGER BERBANTUKAN SOFTWARE SPARKOL VIDEOSCRIBE UNTUK MENINGKATKAN PEMAHAMAN MATEMATIS SISWA - Evi Widayanti; Siti Aisyah (FKIP Universitas Muhammadiyah Prof. DR. HAMKA, 2019)
This study aims to determine the mathematical understanding of students of class X of SMA Muhammadiyah 4 Surabaya. From the result of the test, it is known that the mathematical understanding of class X IPA of SMA Muhammadiyah 4 Surabaya is low. To overcome this, applied treffinger learning model with software sparkol videoscribe. The research method used is a Class Action Research (PTK) with a collaborative pattern. From this study, it can be seen that there is an average increase from 48,62 (low) to 80,34 (good). In addition, it can be known that the ability to reiterate the concept learned has increased from 58.62% to 72.41%; Ability to apply the concept algorithmically increased from 41.38% to 86.21%; Ability to give examples and counter-example of the concepts studied increased from 20.69% to 58.62%; Ability to present concepts in various forms mathematical representation increased from 10.34% to 79.31%; and Ability to link various concepts (internal and external mathematics) increased from 0% to 24.14%. Based on the findings in this study, the treffinger learning model using the software sparkol videoscribe can be used as an alternative to improve students' mathematical understanding.